2021
DOI: 10.3390/cancers13071523
|View full text |Cite
|
Sign up to set email alerts
|

Feasibility and Early Clinical Experience of Online Adaptive MR-Guided Radiotherapy of Liver Tumors

Abstract: Purpose: To assess the feasibility and early results of online adaptive MR-guided radiotherapy (oMRgRT) of liver tumors. Methods: We retrospectively examined consecutive patients with primary or secondary liver lesions treated at our institution using a 0.35T hybrid MR-Linac (Viewray Inc., Mountain View, CA, USA). Online-adaptive treatment planning was used to account for interfractional anatomical changes, and real-time intrafractional motion management using online 2D cine MRI was performed using a respirato… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
25
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 38 publications
(32 citation statements)
references
References 44 publications
2
25
0
Order By: Relevance
“…One of the previously mentioned US-American studies provided data on treatment outcome: Rosenberg et al reported a LC of 80% at the median follow-up of 21.2 months (40). Furthermore, Rogowski et al described a local control rate of 100%, however with a median follow-up of 5 months (41). Preliminary LC results are therefore so far comparable to non-MRI-guided liver SBRT, as recently described in a systematic review by Ohri et al with a LC after 1and 2-years of 90 and 79% (43).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…One of the previously mentioned US-American studies provided data on treatment outcome: Rosenberg et al reported a LC of 80% at the median follow-up of 21.2 months (40). Furthermore, Rogowski et al described a local control rate of 100%, however with a median follow-up of 5 months (41). Preliminary LC results are therefore so far comparable to non-MRI-guided liver SBRT, as recently described in a systematic review by Ohri et al with a LC after 1and 2-years of 90 and 79% (43).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, Rogowski et al. described a local control rate of 100%, however with a median follow-up of 5 months ( 41 ). Preliminary LC results are therefore so far comparable to non-MRI-guided liver SBRT, as recently described in a systematic review by Ohri et al.…”
Section: Discussionmentioning
confidence: 99%
“…The increasing use of SBRT has led to accumulating evidence suggesting that SBRT is an effective and safe treatment option for HCC. Other, more elaborate radiation-based techniques, such as proton radiotherapy ( 18 ) or MR-guided radiation therapy ( 19 , 20 ), are currently emerging in the treatment of liver tumors. However, access to these treatments is still limited today.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to physical compatibility, the radiation oncologists should carefully evaluate the general clinical status of the patient, especially with regard to the required degree of compliance and in consideration of the clinical benefits expected from the use of oMRgRT. Treatment slots for online adaptive treatments using full online replanning are significantly longer than on conventional linacs and can last up to 60 minutes [30,31,36,49,58,59]. Elderly age and frailty do not represent direct exclusion criteria, and specific scoring systems can be used as decisional support systems [50].…”
Section: Mr-specific Patient Selection and Indications For Mr-linacmentioning
confidence: 99%